An exploration of the global development of emerging country multinationals : a study of strategic ambitions and talent management in China and India - Liu, Yi (Curtin University, 2012)
Since Jim O’Neill, the Goldman Sachs economist, coined the acronym of the BRIC countries in 2001 the concept has attracted an infectious logic. The growth of the four BRIC countries, Brazil, Russia, India, and China, is evidenced by their emergence as the most rapidly industrialising countries. These BRIC countries represent a building block for powerful annual events, the first conducted on the sidelines of the United Nations in 2006, then in 2010, and then most recently in New Delhi in March, 2012. In broad terms, Brazil has been considered as the world farm, Russia as an enormous gas station, India as the back office, and China as the factory floor. Collectively, the group represents a quarter of the world’s GDP, almost one half of the gold reserves, nearly 30 per cent of the total land mass, and over 40 per cent of the international population. During the past 10 years their combined growth has been favourably comparable to the world economy including the modern Japan and Germany. Estimates are that by 2050 the combined values of the real, rouble, rupee, and renminbi are expected to eclipse that of today’s richest countries. The heightened importance of China and India are the focus of the investigation reported in this Dissertation.The remarkable economic growth of China and India has drawn a considerable amount of attention. The trajectory of their internationalisation process along with the unique strategic management approaches has effectively facilitated the global economic integration of these two nations. Despite extensive investigations of emerging country multinationals (ECMs) from China and India a lack of attention has been given to the accumulated legacies of managerial mindsets, and cultural priorities, that impact the competitive dynamics of these two nations. As these ECMs hold prominent economic positions in the global arena it is surprising there has not been more rigorous and systematic investigation to establish if specifically Western talent management systems are being incorporated into the traditional nuances of the ECMs. Consequently, this study was undertaken to identify how Chinese and Indian ECMs strategically integrate resources at the international level to attain global business success. The findings of this research have potential to contribute to the generation of theoretical and empirical paradigms that will assist the understanding of the processes of fusion between Western and Eastern theories, and especially the Chinese and Indian contexts.This research employed a mixed method, which incorporated both the quantitative assessment (e.g., questionnaire) and the qualitative technique (e.g., interviews). Several scholars have convincingly argued that culturally related investigations are likely to be enhanced when employing both quantitative and qualitative assessments. Several pilot studies were undertaken with Chinese and Indian respondents in an endeavour to establish the literal meaning of the survey instrument, which was developed by employing the back translation procedure. A feature of the quantitative dimension of this study was the use of an extensive questionnaire, which enabled the collection of data to establish the foundations for evaluating the constructs of talent management, the global business system development as well as the global ambition vision and the connections of these variables in a research model that incorporated the investigation of mediating influences.The research targeted owners or executive managers of ECMs in China and India, who were business executives, selected for their overall successful business and managerial careers in their respective organisations as well as their contribution in strategic decision making for facilitating the global ambition of their firms. A total of 50 Chinese and 51 Indian managers completed a complex questionnaire, and the demographic and organisational attributes of these respondents was also captured in the questionnaire. To complement the quantitative technique and to gain a more comprehensive understanding of the quantitative findings, interviews (21 participants from each country) were undertaken with representatives of the senior managers or owners of ECMS in China and India, who completed the questionnaire. The exceedingly rich and extensive information provided by these respondents was recorded and evaluated with Nvivo software and presented in diagrammatic formats and elucidated with accompanying text.Several statistical analyses were employed to evaluate the quantitative data. For instance, exploratory factor analysis and reliability assessments were conducted to assess the psychometric properties of the instruments, and the results revealed the instruments had robust validities and reliabilities. To test the numerous relationships of the study research model, that was generated from the relevant literature, several vbivariate relationship assessments such as correlation, regression, mediated regression as well as path analyses were performed. These analyses provided two broad patterns of results. One outcome was the generation of a number of creditable instruments, while a second achievement was the detection of relationships with task acquisition practices and institutional global business systems, particularly in the Chinese data. Nevertheless, the fuller results demonstrated a large number of the hypothesised connections were not significantly substantiated, and this observation provided a fruitful platform for further investigation with the qualitative assessments to better understand alternative frameworks to the predicted connections between the constructs.Independent interviews were undertaken with 21 Chinese and 21 Indian senior executives of the ECMs. A salient observation was both the Chinese and the Indian managers highlighted the significant importance of acquiring and maintaining highly skilled and experienced talents in their ECMs, but the challenge of retaining these managerial personnel was escalating and to minimise the implications of talent shortages compelled the ECMs to install a wide range of relevant human resource management practices and mechanisms. One important dimension of the analysis of the qualitative responses was both the Chinese and Indian managers perceived that the strategic ambition of their company was driven by a wide range of external and internal forces. The external forces gave ‘push’ and ‘pull’ market and monetary influences, while local regulations obliged ECMs to operate within compliance and regulatory local frameworks to be aligned with the prominent aspects of government policies.Furthermore, the qualitative analytic results revealed that the rich and dynamic Chinese and Indian cultures significantly influenced how the ECMs develop their global business systems to become global players. Collectively, these factors when coupled with personal differences in values, expectations and belief systems lead to the development of institutional architectures flavoured with crossvergence approaches for the managing of global operations. In short, the Chinese and Indian ECMs are adapting in the pursuit of global business sustainability. Evidence generated from the Chinese and Indian respondents is shown as results in Chapter Four to demonstrate a number of key similarities and differences in the formulation of internationalisation strategies to achieve global ambitions. Elucidation of the comprehensive set of results is systematically undertaken in Chapter Five to provide a greater appreciation of the relativity between the study findings and the research questions.The implications of this study can be founded on theoretical and empirical grounds. The first contribution of this study is advancement to the existing theories and models for internationalisation that were outlined in Chapter Two. The evidence obtained by undertaking this study is that the theoretical conceptions will benefit by a greater inclusion of the national country nuances more as mainline central dimensions of the model rather than as mediating influences. A second theoretical contribution of the study was to evaluate the credibility of Western assumptions in non Western contexts, and while these Western theories provided useful foundation their translation in explaining business philosophies in a non Western economies notions of abstraction will require greater development to focus on elements of cultural relativity. Furthermore, this research can potentially make a third contribution in providing valuable information for gaining a more comprehensive and systematic understanding of business concepts in the Eastern business environments, especially the Chinese and Indian contexts. In addition to these theoretical contributions empirical benefits were acquired.Undertaking this study had three practical achievements. The first empirical contribution is the generation of sound inaugural seven point Likert scales, constructed especially for this study from the relevant literature, that can be used in Chinese and Indian institutions. A second empirical contribution is the revelation Western management strategies and approaches did not readily translate into operational practices in a non Western business environment of the ECMs. It was suggested by the respondents (of the qualitative study design feature) the differences in patterns of operations in their countries were substantially influenced by political restrictions and regulations that allowed institutions to embark on business destinies. A third practical contribution is to provide a greater, more complete and dynamic picture of how firms in emerging countries develop their strategies for pursuing global ambitions, and especially the Chinese and Indian ECMs. This research provides additional insights by examining managerial viewpoints of whether their organisations’ global business system development has an impact on achieving global ambitions.Three prominent concluding features have emerged from this research. Firstly, the concepts and constructs being developed and tested in the Western literature might be used in the Eastern contexts, but considerable attention should be paid to the cultural nuances and the institutional forces. More specifically, the national culture underpins the management philosophies of a particular firm, and in turn these business practices were determined by the political frameworks in which the organisations are operating. Arguably, the importance of culture and institutional architectures are deemed as cornerstones for facilitating the pursuit of global ambitions. Secondly, the results of this study suggest that the employed Western developed terminologies in the study questionnaire did not fully address the business ideology of the Chinese and Indian ECMs.One possible explanation is that the literal meaning of the words and phrases might not have been entirely transmitted and conceptualised when the questionnaire was administrated to capture the Chinese and Indian responses, and such an observation maybe linked to the cultural differences as well as the background of the individual participants. Finally, the combination of both quantitative and qualitative approach in cross cultural setting studies is likely to yield a more insightful understanding of the study findings. Consequently, the study findings suggested that the qualitative assessment is an essential technique to capture information that was not attainable through the more confined quantitative approach, and cross cultural studies can be better facilitated when a mix method design is employed.